Wilbur Wright and Orville Wright papers - McFarland, Marvin Wilks, 1919-; Wright, Milton, 1828-1917.; Wright, Orville, 1871-1948.; Wright, Wilbur, 1867-1912.; United States. National Advisory Committee for Aeronautics; Wright and Wright; Wright Cycle Company
Correspondence, diaries, notebooks, writings, business and legal papers, genealogical material, patents, blueprints, photographs, printed material, and other papers documenting the lives and work of the Wright brothers who designed, built, and piloted the first machine to achieve powered, sustained flight in 1903 and the first practical airplane in 1905.
The papers include scientific data, formulas, and computations related to aerodynamic and design factors and describe the brothers' experimentation with flight at Kitty Hawk, N.C., 1900-1903, at College Park, Md., in 1909, and at Montgomery, Ala., in 1910, and their trips abroad making flight demonstrations. Subjects include the sale of the Wright airplane to the U.S. Army and others; business concerns involving the Wright Company, Flint and Company, Brewer and Son, Thierry Brothers, and companies established in Great Britain, France, and Germany to produce and sell Wright aircraft; the Wright brothers' patents in the U.S. and abroad as well as airplane patents by others; and the brothers' dispute with Smithsonian Institution over whether S.P. Langley had created an aircraft capable of flight prior to the Wrights' flight in December 1903.
Also includes journals and ledgers from Wright and Wright printing company and Wright Cycle Company; records of the U.S. National Advisory Committee for Aeronautics; typescripts, research material, and photographs collected for The Papers of Wilbur and Orville Wright, edited by Marvin Wilks McFarland and published in 1953; and Wright family papers including transcripts of Milton Wright's diaries, 1901-1907.
Wright family correspondents include Katharine Wright Haskell, Lorin Wright, Milton Wright, and Reuchlin Wright. Other correspondents include Henry Harley Arnold, Hart O. Berg, Griffith Brewer, Octave Chanute, Robert J. Collier, Earl N. Findley, Benjamin Delahauf Foulois, Fred C. Kelly, Roy Knabenshue, Frank Purdy Lahm, Charles A. Lindbergh, Grover Cleveland Loening, Glenn L. Martin, Charles Stewart Rolls, G.A. Spratt, Paul Tissandier, Harry A. Toulmin, and Pliny W. Williamson.
Selected material also available through the Library of Congress Web site.
Microfilm edition of selections available
Microfilm addition of diaries available
Microfilm edition of scrapbooks available
Microfilm produced from originals in the Manuscript Division.
Library of Congress Prints and Photographs Division.
Keywords: Arnold, Henry Harley, -- 1886-1950 -- Correspondence; Berg, Hart O., -- 1865-1941 -- Correspondence; Brewer, Griffith, -- 1867-1948 -- Correspondence; Chanute, Octave, -- 1832-1910 -- Correspondence; Collier, Robert J. -- Correspondence; Findley, Earl N. -- 1878-1956 -- Correspondence; Foulois, Benjamin Delahauf, -- 1879-1967 -- Correspondence; Haskell, Katharine Wright, -- 1874-1929 -- Correspondence; Kelly, Fred C. -- 1882-1959 -- Correspondence; Knabenshue, Roy, -- -1960 -- Correspondence; Lahm, Frank Purdy, -- 1877-1963 -- Correspondence; Langley, S. P. -- 1834-1906.; Lindbergh, Charles A. -- 1902-1974 -- Correspondence; Loening, Grover, -- 1888-1976 -- Correspondence; Martin, Glenn L. -- 1886-1955 -- Correspondence; Rolls, Charles Stewart, -- 1877-1910 -- Correspondence; Spratt, G. A. -- 1880-1934 -- Correspondence; Tissandier, Paul, -- 1881- -- Correspondence; Toulmin, Harry A. -- -1942 -- Correspondence; Williamson, Pliny W., -- -1958 -- Correspondence; Wright, Lorin -- Correspondence; Wright, Milton, -- 1828-1917 -- Correspondence; Wright, Reuchlin -- Correspondence; Wright family; Wright family -- Correspondence; United States. -- Army -- Procurement; Brewer and Son; Flint and Company; Smithsonian Institution; Thierry Brothers; Wright Company; Aeronautics; Aircraft industry -- France; Aircraft industry -- Germany; Aircraft industry -- Great Britain; Aircraft industry -- United States; Airplanes; Bicycle industry -- Ohio -- Dayton; Flight; Patents; Printing -- Ohio -- Dayton; Wright Flyer (Airplane); College Park (Md.) -- History; Kitty Hawk (N.C.) -- History; Montgomery (Ala.) -- History; Aviators; Inventors